The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.2320/matertrans.m2009308
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Corrosion Properties of Mg-<I>x</I>Sn-5Al-1Zn (<I>x</I>=0, 1, 5 and 9 mass%) Alloys

Abstract: In the present work, the corrosion properties of Mg-xSn-5Al-1Zn (x ¼ 0, 1, 5 and 9 mass%) alloys have been investigated. Potentiodynamic polarization and immersion tests were carried out in 3.5% NaCl solution of pH 7.2 at room temperature to measure the corrosion properties of Mg-xSn-5Al-1Zn (x ¼ 0, 1, 5, and 9 mass%) alloys. Microstrucral analysis shows the Mg 17 Al 12 and Mg 2 Sn phase were mainly precipitated along grain boundaries. With increase of the Sn contents, the volume fraction of the secondary phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 25 publications
(21 reference statements)
1
11
0
1
Order By: Relevance
“…Bowles et al 39) reveals that the addition of tin reduces the free corrosion potential in comparison to pure magnesium. Park et al 40) reported that the presence of Sn stabilized the Mg(OH) 2 layers and decreased anodic current density. However, the decreasing extent of pit density for SHT samples was slight.…”
Section: Pit Distribution Of Mg-(2 5 8)%sn Alloysmentioning
confidence: 99%
“…Bowles et al 39) reveals that the addition of tin reduces the free corrosion potential in comparison to pure magnesium. Park et al 40) reported that the presence of Sn stabilized the Mg(OH) 2 layers and decreased anodic current density. However, the decreasing extent of pit density for SHT samples was slight.…”
Section: Pit Distribution Of Mg-(2 5 8)%sn Alloysmentioning
confidence: 99%
“…This infers that adding Sn potentially helps to enhance the mechanical integrity of the alloy at elevated temperatures [5,6,7,8,9]. On this account, the Mg–Sn-based alloy system is one of the most extensively studied alloys in recent years [6,7,8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…These goals represent a number of challenges that need to be addressed by both existing and next generation materials for the automotive industries. Magnesium (Mg) alloys and its composites are attractive candidates as alternative materials due to their high specific strength, which can lead to improved fuel efficiency and overall performance through weight reductions [1][2][3]. In particular, Mg-based metal matrix composites (MMCs) are proving to be attractive materials in terms of tribological and high-temperature applications for the construction of pistons, brake rotors, cylinder bores, and cylinder liners in automobiles due largely to their higher specific modulus, stiffness, and wear resistances [4,5].…”
Section: Introductionmentioning
confidence: 99%